CONSTANTINOPLE HAYES 8 - A RARE JUDEO-CHRISTIAN LAMP TYPE IN THE PROVINCE OF SCYTHIA. SEVERAL CONSIDERATIONS DERIVED FROM ITS ICONOGRAPHY AND DISTRIBUTION - Ioan Carol OPRIȘ (Journal of Ancient History and Archaeology, 2020)
The article is specifically tackling the Constantinople Hayes 8 type of clay lamps, dating from the second half of the 5th century to early 7th century AD. Our analysis pinpoints the sites where such lighting devices have been found in the Balkans, along the Lower Danube and in the Black Sea basin, as well as their specific clustering (namely at Constantinople, in association to the Church of St. Polyeuktos at Saraçhane, at Halmyris in the Lower Danube province of Scythia, as well as at Tauric Chersonesos in Northern Pontus). The keywords for understanding these lamps are urban sites, maritime or river distribution, the connection to pilgrims and pilgrimage sites, Eastern Mediterranean and Pontic trade network, not to forget the annona maritime route within the Quaestura Iustiniana exercitus. Considering the uncommon canopy on the discus and based upon known archaeological evidence and contexts, our clay lamps are arguably embodying concurrent plebeian iconic ways and profound symbolic multiplications of the Holy City with the Edicule of the Holy Sepulchre